Mutational analysis of a conserved motif of Agrobacterium tumefaciens VirD2. - Vogel, A M (1995)
The VirD2 polypeptide from Agrobacterium tumefaciens, in the presence of VirD1, introduces a site- and strand-specific nick at the T-DNA borders. A similar reaction at the origin of transfer (oriT) of plasmids is essential for plasmid transfer by bacterial conjugation. A comparison of protein sequences of VirD2 and its functional homologs in bacterial conjugation and in rolling circle replication revealed that they share a conserved 14 residue segment, HxDxxx(P/u)HuHuuux [residues 126-139 of VirD2; Ilyina, T.V. and Koonin, E.V. (1992) Nucleic Acids Res. 20, 3279-3285]. A mutational approach was used to test the role of these residues in the endonuclease activity of VirD2. The results demonstrated that the two invariant histidine residues (H133 and H135) are essential for activity. Mutations at three sites, histidine 126, aspartic acid 128 and aspartic acid 130, that are conserved in a subfamily of the plasmid mobilization proteins, led to the loss of VirD2 activity. Aspartic acid at position 130, could be substituted with glutamic acid and to a much lesser extent, with tyrosine. In contrast, another conserved residue, asparagine 139, tolerated many different amino acid substitutions. The non-conserved residues, arginine 129, proline 132 and leucine 134, were also found to be important for function. Isolation of null mutations that map throughout this conserved domain confirm the hypothesis that this region is essential for function.